Рассказы - Аксаков Сергей Тимофеевич (Библиотечка школьника, 2015)
Экземпляры: Ф. 12 (20230721) / Инвентарный номер: 50007 / Цена: 120.00 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: А 41 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Рус)1